ANALISIS ICMP MODIFIKASI TERHADAP NONLINEAR TIME HISTORY DAN PUSHOVER DALAM MODEL BANGUNAN 2-D MULTI STOREY - Adiputro, Susanto Triyogo; Soegiarso, Roesdiman; Prabowo, Andy (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
Improved Concecutive Modal Pushover (ICMP) method is proposed to improve the conventional Pushover in estimating earthquake demands on tall buildings. This method accounts for inelastic material properties and interaction between vibration modes. The incremental displacement at the building roof used in each stage of the pushover analysis is modified based on the displacement contribution of each mode. This study proposes an improved of the existing ICMP method by modifying the vibration mode variations in the pushover analysis. The performance of the modified ICMP method is verified against a wide variety of modes to determine the lateral forces of various building conditions. The results obtained from the modified ICMP method are compared with the results from Nonlinear Response History Analysis (NLHRA), and conventional pushover analysis, as well as the original ICMP method. The comparison shows that the results obtained from the modified ICMP method with mode variation of S1 (100% M), S2 (90% M1 + 10% M2), and S3 (80% M1 + 20% M3), are closer than the original ICMP using 100% participation of modes 1, 2, and 3. The modified ICMP yields an underestimate results against the original ICMP in the context of displacement response by not more than 30% Abstrak Metode Improved Concecutive Modal Pushover (ICMP) diusulkan untuk meningkatkan Pushover konvensional dalam memperkirakan tuntutan gempa pada bangunan tinggi. ICMP menyumbang sifat struktural inelastik dan interaksi antara mode getaran. Perpindahan kenaikan diatap bangunan yang digunakan dalam setiap tahap analisis pushover dimodifikasi berdasarkan pada kontribusi perpindahan masing-masing mode. Kinerja prosedur Pengembangan ICMP yang diusulkan diverifikasi terhadap berbagai macam variasi mode untuk menentukan lateral force dari berbagai kondisi bangunan. Hasil yang diperoleh dari prosedur pengembangan ICMP dibandingkan dengan hasil dari Nonlinear Response History Analysis (NLHRA), analisis pushover konvensional, dan analisis ICMP. Perbandingan hasil ketiga metode menunjukkan kelebihan pengembangan ICMP variasi S1 (100% M) S2 (90%M1 + 10%M2) S3 (80%M1+20%M3), lebih mendekati dibandingkan proposi ICMP sebelumnya yang menggunakan 100% partisipasi mode 1, 2, dan 3. Hasil pengembangan ICMP juga memberikan hasil yang baik dengan rentang underestimate dibawah, terhadap ICMP pada konteks respons displacement tidak lebih dari 30%.